T cells mediate cell non‐autonomous arterial ageing in mice. (12th August 2021) - Trott, Daniel W.; Machin, Daniel R.; Phuong, Tam T. T.; Adeyemo, AdeLola O.; Bloom, Samuel I.; Bramwell, R. Colton; Sorensen, Eric S.; Lesniewski, Lisa A.; Donato, Anthony J.
Abstract : Key points: Increased large artery stiffness and impaired endothelium‐dependent dilatation occur with advanced age. We sought to determine whether T cells mechanistically contribute to age‐related arterial dysfunction. We found that old mice exhibited greater proinflammatory T cell accumulation around both the aorta and mesenteric arteries. Pharmacologic depletion or genetic deletion of T cells in old mice resulted in ameliorated large artery stiffness and greater endothelium‐dependent dilatation compared with mice with T cells intact. Abstract: Ageing of the arteries is characterized by increased large artery stiffness and impaired endothelium‐dependent dilatation. T cells contribute to hypertension in acute rodent models but whether they contribute to chronic age‐related arterial dysfunction is unknown. To determine whether T cells directly mediate age‐related arterial dysfunction, we examined large elastic artery and resistance artery function in young (4–6 months) and old (22–24 months) wild‐type mice treated with anti‐CD3 F(ab'2) fragments to deplete T cells (150 μg, i.p. every 7 days for 28 days) or isotype control fragments. Old mice exhibited greater numbers of T cells in both aorta and mesenteric vasculature when compared with young mice. Old mice treated with anti‐CD3 fragments exhibited depletion of T cells in blood, spleen, aorta and mesenteric vasculature. Old mice also exhibited greater numbers of aortic and mesenteric IFN‐γ and TNF‐α‐producing T cells when compared with young mice. Old control mice exhibited greater large artery stiffness and impaired resistance artery endothelium‐dependent dilatation in comparison with young mice. In old mice, large artery stiffness was ameliorated with anti‐CD3 treatment. Anti‐CD3‐treated old mice also exhibited greater endothelium‐dependent dilatation than age‐matched controls. We also examined arterial function in young and old Rag‐1 –/– mice, which lack lymphocytes. Rag‐1 –/– mice exhibited blunted increases in large artery stiffness with age compared with wild‐type mice. Old Rag‐1 –/– mice also exhibited greater endothelium‐dependent dilatation compared with old wild‐type mice. Collectively, these results demonstrate that T cells play an important role in age‐related arterial dysfunction. Key points: Increased large artery stiffness and impaired endothelium‐dependent dilatation occur with advanced age. We sought to determine whether T cells mechanistically contribute to age‐related arterial dysfunction. We found that old mice exhibited greater proinflammatory T cell accumulation around both the aorta and mesenteric arteries. Pharmacologic depletion or genetic deletion of T cells in old mice resulted in ameliorated large artery stiffness and greater endothelium‐dependent dilatation compared with mice with T cells intact.